2005
DOI: 10.1002/pca.859
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition of the epicuticular wax from the fruits ofEucalyptus globulus

Abstract: The chemical composition of the epicuticular wax from the fruits of Eucalyptus globulus was studied by GC-MS before and after alkaline hydrolysis. The wax had two main components, ursolic acid and tritriacontan-16,18-dione, together with several other triterpenic acids. After alkaline hydrolysis, a large increase in the amounts of triterpenic acids and fatty acids (particularly in hexadecanoic acid) was observed, suggesting that these components were present predominantly in esterified forms in the fruit wax. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…Currently, work is under way at our laboratory to identify the chemical constituents of this fraction. Some published works show that the analysable percentage depends on species and the extract composition, and can be even lower [8][9][10].…”
Section: Resultsmentioning
confidence: 97%
“…Currently, work is under way at our laboratory to identify the chemical constituents of this fraction. Some published works show that the analysable percentage depends on species and the extract composition, and can be even lower [8][9][10].…”
Section: Resultsmentioning
confidence: 97%
“…cv. Howesα-amyrin; β-amyrin; α-amyrin acetate; β-amyrin acetate; methyl oleanolate; methyl ursolate; oleanolic acid; β-sitosterol; stigmasterol; usolic acid,47.6 % of the total wax extractUrsolic acid (20 % of the total wax extract)Immersion of whole fruits in chloroformGC–MSCroteau and Fagerson (1971)Eggplant ( S. melongena L.)α-amyrin; β-amyrin; germanicol; lupeol; β-sitosterol; stigmasterol2.9 % of the total wax extract (average from 3 cultivars)Lupeol (0.74 % of wax extract)Dipping of whole fruits into tert -butylmethyl ether in ultrasonic bathGC–MSBauer et al (2005) E. globulus Labill.3-acetyl-oleanolic acid; betulinic acid; betulonic acid; 3β,11α-dihydroxyurs-12-en-28-oic acid; 3β-dihydroxyurs-11-en-13β(28)-olide (ursolic acid lactone); oleanolic acid; ursolic acid34.4 % of the total wax extractUrsolic acid (17.1 % of wax extract)Dipping of whole fruits into boiling mixture of acetone/light petroleum (1:1)GC–MSPereira et al (2005)Grapefruit ( Citrus paradisi Macf.) cv.…”
Section: Other Fruits With Edible Peelmentioning
confidence: 99%
“…Knowledge of the chemical composition of these unused plant parts could help to solve the problem of this waste material and increase the economic value of E. globulus cultivation. The cuticular wax of E. globulus fruit was shown to contain a significant amount of triterpenoids (34.4 % of the total wax extract), including ursolic acid, which accounted for 17.1 % of total wax, and an interesting series of other triterpene acids, such as 3-acetyl-oleanolic acid, betulinic acid, betulonic acid, 3β-dihydroxyurs-11-en-13β(28)-olide (ursolic acid lactone), oleanolic acid and 3β,11α-dihydroxyurs-12-en-28-oic acid (Table 2), the last of which was identified for the first time (Pereira et al 2005). Betulinic acid, usually obtained from the bark of the white birch Betula alba L., has been shown to possess a variety of biological properties including antibacterial, anti-HIV, antimalarial, antiinflammatory and anthelmintic activities (Yogeeswari and Sriram 2005).…”
Section: Inedible Fruitsmentioning
confidence: 99%
“…2). Comparison of the H-11 and C-11 signals of 1 with those previously reported for 3b,11a-dihydroxyurs-12-en-28-oic acid at d H 3.99 (H-11) and d C 65.8 (C-11) (Pereira et al, 2005) and 11a-hydroxy-b-amyrin at d H 4.19 (H-11) and d C 67.6 (C-11) (Seki et al, 2008) revealed that the signals of H-11 (d H 4.38) and C-11 (d C 81.2) of 1 were shifted downfield. These observations suggested the presence of the 11a-hydroperoxy group (Kuo and Chiang, 2000;Song et al, 2008) which was further supported by the 1 H and 13 C chemical shift of 1 in accordance with H-11 (d H 4.48) and C-11 (d H 81.0) of 11a-hydroperoxy-diacetyl-hederagenin (Chávez and Delgado, 1994).…”
Section: Resultsmentioning
confidence: 97%